PERSISTENSI KINERJA REKSADANA SAHAM DAN REKSADANA PENDAPATAN TETAP DI INDONESIA - , Albertus Dedy Hartarto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to find empirical evidence that there is performance persistence in equity fund and fixed-income funds in Indoneia. The data in this study are all fixed income mutual fund shares are registered in the Bapepam-LK in the period January 2005 - December 2008. This research uses the method of rate of return and the Sharpe index results from both methods will be displayed in the form of winner - Losser contingency tables. Results of this study showed that there performance persistence on equity funds and fixed income funds in Indonesia.